Small Scales Food Milling Industries in Dschang-Cameroon: Socio-Economic and Technical Characteristics Assessment - Tchoumboue, Nsah-ko (Discoveries in Agriculture and Food Sciences, 2025)
Food security in Africa mostly depends on Food milling industries. Until now lack of institutional rules and hygiene are some of the main causes responsible of low performances of food milling industries in Africa. The purpose of this work is then to analyze the socio-economic and technical characteristics of local mills in order to improve their performance. At this effect, a survey was conducted on 99 food milling industries randomly selected in Dschang city town. Direct measurements and observations were also carried out using specified tools. The collected data were codified using Microsoft Excel 2021. The descriptive analyses were performed using SPSS 21.0. The main results of this work were as follows: women are more involved in the food milling activities. Almost all the food milling industries (92.6%) possess Hammer mill and Flattener mill machine to grind dry foodstuffs and wet foodstuffs respectively. Machine capacities are still low which vary from the highest values of 30 kg per hour to the lowest value of 10 kg per hour. Based on number of working machines, 9 categories of industries were identified. The lifespan of those machines ranges from 5 to 7 years. None of the machines (0%) in industries possess the manual operation to carry out maintenance and provide healthy practices in food milling. Around 90% of the milling machines are made from metals and iron materials with industrial paints that could have negative effects on food quality. Law regulation related to lifespan and Machine’s design should be put in place in order to Protect consumers from food spoilage and intoxication by bacterial and ferrous contamination.